Interpreting the Consequences of Midwestern Agricultural Industrialization - King, Martin Burce (Journal of Economic Issues (Association for Evolutionary Economics), 2000)
The article focuses on the interpretation of consequences of Midwestern agricultural industrialization. The nature and consequences of the industrialization of agriculture are well documented in academic research and in the popular press. Interpretations of the process vary in reflection of the diverse perceptions of the nature and overall significance of industrialization. Suggested policies range from a "hands-off" to a "prohibit and prevent wherever possible" approach. Both approaches are unrealistic because they fail to recognize the historical context in which agricultural industrialization is taking place. In this paper, the author presents a historical context for the process, using nineteenth-century Illinois and the industrialization of swine production as examples of commercialization and industrialization of Midwestern agriculture, respectively. The author integrates the work of Karl Polanyi and K. William Kapp into the discussion to provide a foundation for realistic policy and to demonstrate the relevance of an institutionalist perspective to the formation of contemporary agricultural policy.
Economics
Keywords: KAPP; Karl William; agriculture; commercialization; crop insurance; economic theory; evolutionary economics; industrialization; production (economic theory); rural industries